2004
DOI: 10.1158/0008-5472.can-03-3090
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin-3F Is an Inhibitor of Tumor Angiogenesis

Abstract: The neuropilin-1 (np1) and neuropilin-2 (np2) receptors form complexes with type-A plexins. These complexes serve as signaling receptors for specific class-3 semaphorins. Np1 and np2 function in addition as receptors for heparin-binding forms of vascular endothelial growth factor (VEGF), such as VEGF 165 . Human umbilical vein endothelial cells (HUVEC) express tyrosine-kinase receptors for VEGF and basic fibroblast growth factor (bFGF), as well as np1, np2, and several type-A plexins. We have found that semaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
194
3
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(209 citation statements)
references
References 47 publications
7
194
3
5
Order By: Relevance
“…Sema3F, another inhibitor of angiogenesis, functions as a more global inhibitor in that it blocks angiogenesis in response to both VEGF and bFGF. 28,29 However, as we demonstrate, it does not induce VP (Figure 3). This may be caused by differential binding of these 2 proteins to their Nrp receptors, since Sema3A and Sema3F ligate Nrp-1 and Nrp-2, respectively.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Sema3F, another inhibitor of angiogenesis, functions as a more global inhibitor in that it blocks angiogenesis in response to both VEGF and bFGF. 28,29 However, as we demonstrate, it does not induce VP (Figure 3). This may be caused by differential binding of these 2 proteins to their Nrp receptors, since Sema3A and Sema3F ligate Nrp-1 and Nrp-2, respectively.…”
Section: Discussionsupporting
confidence: 56%
“…However, it inhibits both VEGF-as well as bFGF-induced angiogenesis, indicating that it plays a broader role than Sema3A in regulating blood vessel formation. 28,29 To determine if other class 3 semaphorins can induce VP, we compared the effects of Sema3A, Sema3F, and Sema3B on permeability. Unlike Sema3A, subcutaneous injection of Sema3F or Sema3B did not lead to VP (Figure 3), suggesting that Sema3B and Sema3F are functionally distinct from Sema3A with respect to their influence on the biologic properties of blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…77,78 Similarly, Sema3F inhibits cell spreading and migration in breast carcinoma, melanoma and ECs, resulting in reduced metastatic dissemination. [78][79][80] Furthermore, since NP-1 is a receptor for both class III semaphorins and VEGF, class III semaphorins may function as antiangiogenic factors by competitively interfering with VEGF receptors. 68 …”
Section: Sema7a: a Semaphorin Involved In Inflammatory Responses Via mentioning
confidence: 99%
“…Like Sema3A, Sema3F can inhibit angiogenesis and endothelial cell migration but through neuropilin-2 binding. 44,45 SEMA3F overexpression in mouse fibrosarcoma or ovarian cancer cells block their proliferation. 36,46 More recently it was shown that SEMA3F overexpression in highly metastatic melanoma cells (that only express neuropilin-2 and not neuropilin-1, VEGF-R1 or VEGFR-2) inhibits adhesion and migration but not proliferation.…”
Section: Classmentioning
confidence: 99%